2015
DOI: 10.1103/physrevlett.115.196601
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Scattering by Magnetic Impurities as a Model for Spin Relaxation in Bilayer Graphene

Abstract: We propose that the observed spin relaxation in bilayer graphene is due to resonant scattering by magnetic impurities. We analyze a resonant scattering model due to adatoms on both dimer and nondimer sites, finding that only the former give narrow resonances at the charge neutrality point. Opposite to singlelayer graphene, the measured spin-relaxation rate in the graphene bilayer increases with carrier density. Although it has been commonly argued that a different mechanism must be at play for the two structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 50 publications
8
45
0
Order By: Relevance
“…For instance, this source could be magnetic scatterers that have recently been predicted to increase the spin flipping process without having a significant influence on the charge transport. 27,28 To check the role of the magnetic impurities on spin relaxation, we now investigate the carrier concentration dependence of the local device resistance and Prior to the carrier concentration-dependent spin transport measurements, we first performed charge characterizations of both encapsulated and non-encapsulated bilayer graphene junctions at room temperature. Our devices are weakly electron doped, which is possibly because of a charge-transfer process from the MgO layer.…”
Section: Spin Transport In Bilayer Graphenementioning
confidence: 99%
See 3 more Smart Citations
“…For instance, this source could be magnetic scatterers that have recently been predicted to increase the spin flipping process without having a significant influence on the charge transport. 27,28 To check the role of the magnetic impurities on spin relaxation, we now investigate the carrier concentration dependence of the local device resistance and Prior to the carrier concentration-dependent spin transport measurements, we first performed charge characterizations of both encapsulated and non-encapsulated bilayer graphene junctions at room temperature. Our devices are weakly electron doped, which is possibly because of a charge-transfer process from the MgO layer.…”
Section: Spin Transport In Bilayer Graphenementioning
confidence: 99%
“…Such dependencies in both low and high carrier concentration regimes appear to agree with the recent theoretical work where the spin relaxation in graphene is proposed to be dominated by resonant scatterers because of the presence of a low concentration of magnetic impurities, such as polymer residues. 27 In that theory, the inverse dependence of the spin relaxation on the carrier concentration in bilayer and single-layer graphene was attributed to the different scales of energy fluctuations in these two systems because of their different density of states. Away from the puddle regime, the sudden increase in spin-relaxation time at~4-5 × 10 12 cm − 2 , with no corresponding signature in the charge transport, is expected for bilayer graphene because of the scattering from these resonant magnetic scatterers.…”
Section: Spin Transport In Bilayer Graphenementioning
confidence: 99%
See 2 more Smart Citations
“…This can have a considerable impact on electronic transport, as revealed by measurements of a metal-insulator transition with increasing hydrogen density 9 . Recent experimental work has also shown that hydrogen induces a localized magnetic resonance 10 , which could have important implications for graphene spintronics 11,12 . While mechanical exfoliation tends to yield the highest-quality graphene samples in the laboratory, chemical vapor deposition (CVD) is the most efficient method to produce graphene on an industrial scale.…”
Section: Since Its Experimental Isolation In 2004mentioning
confidence: 99%